Surgical Treatment of Chondrodysplasia Punctata Tibial-Metacarpal Type Until Skeletal Maturity: A Case Report. Issue 4 (25th October 2022) - Fujimoto, Yoh; Takikawa, Kazuharu; Takeshita, Yujiro
Abstract : Case: An infant boy with chondrodysplasia punctata tibial-metacarpal type (CDP-TM) was followed up till skeletal maturity. The patient underwent surgeries for bilateral patellar dislocations at the age of 9 years of age, left leg length discrepancy at 12 years, and atlantoaxial subluxation at 14 years. At the final follow-up at 18 years, he had no complaints or limitation of his daily life activities. Conclusion: CDP-TM may require multiple orthopedic surgeries such as patellofemoral instability, limb length discrepancy, and upper cervical dysplasia until skeletal maturity, and should be followed in order to identify them early.